Analysis of the Calculation of Rice Staple Food Reserve Needs in Gorontalo Regency City - Norma Luntayo; Ria Indriani; Asda Rauf (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Rice is a strategic commodity that determines socio-economic stability as well as the main indicator of food security in Indonesia, especially in Gorontalo Province. Based on data for 2024, rice production in Gorontalo has decreased by 6.59%, which has a direct impact on the decline in the availability of rice for the population's consumption. This study aims to (1) analyze the appropriate method of calculating the needs of Rice Staple Food Reserves (CPPB) at the Gorontalo Regency/City level by considering local production, consumption, and risk factor data; and (2) analyze the factors that affect the needs of the CPPB to support the formulation of regional food security policies. The type of research used is quantitative descriptive using secondary data for an annual period from the Central Statistics Agency (BPS), the Agriculture Office, and the Gorontalo Provincial Food Security Office. The data analysis method was carried out through the mathematical formula approach C = (K x P) + R to calculate the ideal reserve volume, as well as multiple linear regression analysis to test the influence of independent variables partially (t-test) and simultaneously (F-test). The results of the study are expected to provide a visualization of real food reserve needs in each region and prove the significant contribution of production, consumption, and local risk factors to fluctuations in basic reserve needs. Strategic recommendations are directed at optimizing local government buffer stocks and food distribution management efficiency to anticipate food crises due to climate dynamics and other local risks